Basic Movement Training Through Traditional Games For Students In Elementary School - Sari, Eka Fitri Novita; Siregar, Nofi Marlina; Ali, Masnur; Asri, Novri (International Journal of Public Devotion, 2025)
This basic movement training through traditional games at SDN 01 Kamasan, Serang Regency, Banten aims to improve students' gross motor skills through fun activities that are relevant to their culture. Traditional games such as congklak, engklek, ucing-ucingan, and gasing were chosen because they contain basic movements such as running, jumping, throwing, and catching that are important for children's physical development. The training was conducted using demonstration, active participation, and group discussion methods. The observation results showed an increase in students' basic movement skills after attending the training. In addition, students also looked more enthusiastic and motivated in participating in learning activities as much as 85% of students. This training is expected to be an effective and fun alternative in developing students' basic movement skills, while preserving the noble values contained in traditional games.Pelatihan Gerak Dasar Melalui Permainan Tradisional untuk Siswa Sekolah DasarABSTRAKPelatihan gerak dasar melalui permainan tradisional di SDN 01 Kamasan, Kabupaten Serang, Banten ini bertujuan untuk meningkatkan kemampuan motorik kasar siswa melalui aktivitas yang menyenangkan dan relevan dengan budaya mereka. Permainan tradisional seperti congklak, engklek, ucing-ucingan, dan gasing dipilih karena mengandung gerakan-gerakan dasar seperti berlari, melompat, melempar, dan menangkap yang penting bagi perkembangan fisik anak. Pelatihan ini dilaksanakan dengan metode demonstrasi, partisipasi aktif, dan diskusi kelompok. Hasil observasi menunjukkan adanya peningkatan kemampuan gerak dasar siswa setelah mengikuti pelatihan. Selain itu, siswa juga terlihat lebih antusias dan termotivasi dalam mengikuti kegiatan pembelajaran sebanyak 85% Siswa. Pelatihan ini diharapkan dapat menjadi alternatif yang efektif dan menyenangkan dalam mengembangkan kemampuan gerak dasar siswa, sekaligus melestarikan nilai-nilai luhur yang terkandung dalam permainan tradisional.Kata Kunci:Gerak dasar; permainan tradisional